Odpowiedź:
[tex]a)\\\\2x^2+3x+1=0\\\\\Delta=b^2-4ac=3^2-4*2*1=9-8=1\\\\\sqrt{\Delta}=\sqrt{1}=1\\\\\\x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-3-1}{2*2}=\frac{-4}{4}=-1\\\\\\x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-3+1}{2*2}=\frac{-2}{4}=-\frac{1}{2}[/tex]
[tex]b)\\\\-3x^2+x+2=0\\\\\Delta=b^2-4ac=1^2-4*(-3)*2=1+24=25\\\\\sqrt{\Delta}=\sqrt{25}=5\\\\\\x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-1-5}{2*(-3)}=\frac{-6}{-6}=1\\\\\\x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-1+5}{2*(-3)}=\frac{4}{-6}=-\frac{2}{3}[/tex]